ONTOLOGY AND POLITICS: FROM DISAGREEMENT TO ABSENCE. THE POLITICAL PHILOSOPHY OF JACQUES RANCIÈRE AND SLAVOJ ŽIŽEK - Karapetrović, Milena (Politeia, 2020)
Understanding the constant transformation of forms of political agency in contemporary age sets a basic requirement for philosophers - to reconsider concepts that seek to theoretically comprehend these changes. Naming, redefining, and rethinking the meanings of classic concepts are not only interventions within the theory, but they also allow for a clearer picture of the future of society and  state. This paper demonstrates how philosophers Jacques Rancière and Slavoj Zizek contribute to this research. The emphasis is only on some of the key points of these two theorists that can be used as an illustration of the main themes within contemporary political philosophy and ontology. Rancière emphasises the point of disagreement as the point from which to begin the analysis of the relationship between philosophy and politics, and uses the following terms: politics (space for the theoretical agency) and police (existing political structures). In this way, a new basis for the debate on universal issues - freedom, justice, equality - is constructed. Zizek puts the ‘absent centre of political ontology’ as the main problem, that is, instead of insisting on subjectivation, one should rethink the classic concept of the subject and expose the shortcomings of the earlier definitions of this concept in order to form the basis for new philosophical approaches. Comparing the views of Rancière and Zizek, the author indicates how the production of knowledge and critical thinking can lead to a clearer view of the (political) subject, and its place and role in new redistributions of power in the public space.
Keywords: Ontology; Politics; Jacques Rancière; Slavoj Zizek; Police; Concepts